Toripalimab in Combination With Induction Chemotherapy and Subsequent Chemoradiation as First-Line Treatment in Patients With Advanced/Metastatic Esophageal Carcinoma: Protocol for a Single-Arm, Prospective, Open-Label, Phase II Clinical Trial (TR-EAT) - Wu, Lei; Wang, Yi; Li, Baisen; Wan, Gang; Liang, Long; Li, Tao; Lang, Jinyi; Wang, Qifeng (Frontiers in Oncology, 2022)
Immune checkpoint inhibitor therapy combined with chemotherapy is safe and effective in treating advanced esophageal carcinoma; however, some patients still experience tumor progression and/or metastasis. Whether the addition of radiotherapy to immunotherapy combined with chemotherapy improves the prognosis of patients with advanced/metastatic esophageal carcinoma needs to be investigated. In the present study, we developed a protocol for our clinical trial indicating that toripalimab combined with induction chemotherapy followed by chemoradiotherapy can safely prolong survival in patients with stage IV esophageal carcinoma. This open-label, single-arm, phase II trial will include patients with unresectable stage IV esophageal squamous cell carcinoma who have not received prior systemic therapy. The patients will be treated with two cycles of toripalimab (240 mg, 1 day before chemotherapy, Q3W) combined with induction chemotherapy (paclitaxel, 135–175 mg/m2 + carboplatin, area under the curve = 4–6, day 1, intravenous, Q3W). Thereafter, they will undergo two cycles of the aforementioned treatment with concurrent radiotherapy (30–50 Gy in 15–25 fractions), followed by toripalimab (240 mg, day 1, Q3W) for 1 year. The primary outcome measure will be progression-free survival; the secondary outcome measures will include the objective response rate, disease control rate, duration of remission, 1- and 2-year overall survival rates, safety and tolerability, and changes in health-related quality of life. The study protocol was approved by the Ethics Committee of Sichuan Cancer Hospital (SCCHEC-02-2021-021). The trial is underway in accordance with the Declaration of Helsinki. Clinical Trial Registration http://www.chictr.org.cn/showproj.aspx?proj=126830, identifier ChiCTR2100046715.